THE INFLUENCE OF BRAND PASSION, BRAND TRUST AND BRAND IMAGE ON BRAND EVANGELISM IN PRODUCTS IPHONE IN LHOKSEUMAWE CITY - Adnan; Rusydi; Zamzami (RADJA PUBLIKA, 2022)
This study aims to analyze the effect of Brand Passion, Brand Trust and Brand Image on Brand Evangelism on Iphone Products in Lhokseumawe City. This study uses primary data obtained by distributing questionnaires to 100 respondents who were selected using the Slovin formula. The data analysis method used is the multiple linear regression method with the help of SPSS. The results showed that brand passion had a negative and insignificant effect on brand evangelism of iPhone product users in Lhokseumawe City, brand trust had a positive and significant effect on brand evangelism of iPhone product users in Lhokseumawe City, brand image had a negative and insignificant effect on brand evangelism of iPhone product users. in Lhokseumawe City, and the test results simultaneously show that the variables of brand passion, brand image and brand trust have a negative and insignificant effect on brand evangelism of iPhone product users in Lhokseumawe City.